The Concept of Education Planning in an Islamic Framework - Irfan Wahyu Syifa; Widhya Nusantari (Universitas Darussalam Gontor, 2021)
This study aims to explore the scientific treasures of Islam, especially in the Qur’an, Sunnah and Shirah Nabawiyah in formulating the ideal Islamic education planning concept along with examples of Islamic educational institutions that have been successful in planning so that they can become references for other Islamic educational institutions. This study uses descriptive qualitative research with data sources from Islamic literature. The results show that planning is a systematic and rational process by analyzing alternatives and any developments in Islamic education in an organization in order to achieve optimal goals in accordance with the worldview of Islam. Islam teaches that all aspects of life must be sourced from primary sources, in several verses of the Qur'an, Sunnah and Shirah Nabawiyah, it has been explained about the core concepts of a comprehensive Islamic education planning. Therefore, planning for Islamic education must be aimed at the interests of society and oriented towards the world and the hereafter.